Technical challenges of e-governance and ways to ensure successful digital transformation in the government sector - Yasser Elamlik Ahmed Seleman; Mustafa Amin Abdelmgeed Mohammed; Nazar kamaleldin Ahmed suliaman (International Journal of Computers and Informatics, 2026)
This study seeks to identify the combined impact of the dimensions of digital governance (technology infrastructure and operational processes, management and authority, accountability and transparency, and digital risk management) on digital transformation. The digital transformation era represents the "application of digital capabilities to processes, products, and assets" with the aim of "improving efficiency, enhancing customer value, managing risks, and unlocking new revenue opportunities." Similarly, digital transformation impacts not only life but also individual experiences. This study focuses on the mechanisms necessary to digitally transform the interaction between governments and citizens to ensure greater transparency, accountability, and integrity. It contributes to defining the current state of e-governance and digital maturity in government institutions.